Comparative study of corrosion behaviour of nickel and gold plated carbon steels used as ornamentals in saline environment (2012)
This study investigated the corrosion resistance of plated and unplated steels useful as ornamentals in saline environment. Nickel plating of carbon steel was done in watts solution for 25minutes with a current density of 3 Adm-3 at 60oC. The nickel plated carbon steel was later gold plated for 20 minutes with a current density of 0.2 Adm-3 at 50oC . The plated and unplated carbon steels were immersed in saline environment for 360 hours. Weight loss was taken every 24 hours in order to evaluate corrosion penetration rate (CPR). The results obtained showed that plated carbon steel generally offers a better corrosion resistance than the unplated one. Corrosion of ornamentals is equally gaining importance especially coated ornamentals. The use of nickel for ornamentals is gaining more prominence over silver rising due to its shiny surface and its cost. The use of nickel plated ornamentals just as gold plated ornamentals are being patronized will surely become common place due to affordability for the generality of people. However, the effects of everyday corrosive fluids from kitchen salt and low acidic media on the durability of the coatings need to be established. Carbon steel is the natural substrate used in ornamental coatings .The results also showed that a small thickness of gold plated carbon steel exhibited better corrosion resistance in saline environment. More also, gold plated carbon steel is found to be more suitable and reliable candidate material than nickel plated carbon steel in this environment although with higher costs.